Use of Cocktail of Bacteriophage for Salmonella Typhimurium Control in Chicken Meat - Garcia-Mena, V; Tello-Reyes, M (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Foodborne diseases are extremely relevant and constitute an area of alert for public health authorities due to the high impact and number of people affected each year. The food industry has implemented microbiological control plans that ensure the quality and safety of its products; however, due to the high prevalence of foodborne diseases, the industry requires new microbiological control systems. One of the main causative agents of diseases transmitted by poultry meat is the bacterium Salmonella enterica. Disinfectants, antibiotics, and vaccines are used to control this pathogen. However, they have not been efficient in the total elimination of these bacteria, with numerous outbreaks caused by this bacterium observed today, in addition to the increase in antibiotic-resistant bacteria. The search for new technologies to reduce microbial contamination in the poultry industry continues to be a necessity and the use of lytic bacteriophages is one of the new solutions. In this study, 20 bacteriophages were isolated for Salmonella spp. obtained from natural environments and cocktails composed of five of them were designed, where three belonged to the Siphoviridae family and two to the Microviridae family. This cocktail was tested on chicken meat infected with Salmonella Typhimurium at 10° C, where it was found that this cocktail was capable of decreasing 1.4 logarithmic units at 48 h compared to the control. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.